Occurrence and consequences of acid sulphate soils and methods of site remediation - Golab, Alexandra N.; Indraratna, Buddhima (Geomechanics and geoengineering : an international journal, 2009)
The oxidation of sulphides in acid sulphate soils (ASS) causes the acidification of many Australian coastal river systems. The acidity negatively impacts upon coastal ecosystems, aquaculture, agriculture and concrete and steel infrastructure. In the low-lying floodplains, relatively deep surface drains fitted with one-way floodgates lower the watertable, thereby exposing the sulphidic minerals to oxidation. On the Broughton Creek floodplain in SE Australia, four distinct remediation strategies have been developed to tackle the issue of acidification by ASS: (i) simple V-notch weirs that raise the level of the watertable surrounding the drains thereby submerging the pyrite and preventing the further formation of acidity; (ii) modified two-way floodgates that allow the inflow of tidal water into the drains, thereby buffering the acidity within the drain before it enters the river and raising the level of the watertable surrounding the drain; (iii) lateral impermeable lime barriers that both prevent oxidation of pyrite by stopping the downward movement of oxygen into the soil and neutralise the acidity in the groundwater; and (iv) permeable reactive barriers (PRB) that passively intercept the groundwater flow and neutralise the acidity. Each remediation strategy has a distinct role to suit the different terrain and groundwater conditions.